2020
DOI: 10.1111/jon.12828
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion and Perfusion MRI Predicts Response Preceding and Shortly After Radiosurgery to Brain Metastases: A Pilot Study

Abstract: To determine the ability of diffusion-weighted imaging (DWI) and dynamic contrastenhanced magnetic resonance imaging (DCE-MRI) to predict long-term response of brain metastases prior to and within 72 hours of stereotactic radiosurgery (SRS). METHODS: In this prospective pilot study, multiple b-value DWI and T1-weighted DCE-MRI were performed in patients with brain metastases before and within 72 hours following SRS. Diffusion-weighted images were analyzed using the monoexponential and intravoxel incoherent mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…In this study, almost all the BM before SRS treatment showed hyper-intensity on DWI sequence, which may relate to the growth pattern of highly infiltrating tumor cells. After treatment, most tumors showed iso-intensity or hypo-intensity on DWI sequences, regardless of whether they were in the IG or PG, which may relate to tumor cell necrosis caused by radiation [ 41 ]. Therefore, there was no statistically significant difference in DWI sequence signals between the IG and PG.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, almost all the BM before SRS treatment showed hyper-intensity on DWI sequence, which may relate to the growth pattern of highly infiltrating tumor cells. After treatment, most tumors showed iso-intensity or hypo-intensity on DWI sequences, regardless of whether they were in the IG or PG, which may relate to tumor cell necrosis caused by radiation [ 41 ]. Therefore, there was no statistically significant difference in DWI sequence signals between the IG and PG.…”
Section: Discussionmentioning
confidence: 99%
“…With conventional MRI of the brain, no discrimination between pseudoprogression and true progression can be made. Advanced imaging techniques can be deployed (see Table 3), [38][39][40][41][42][43][44] but it remains uncertain whether any of these provide sufficient information to discriminate between tumor progression and therapy-related abnormalities.…”
Section: Dynamic Susceptibility Contrastperfusion Imagingmentioning
confidence: 99%
“…On DWI, ADC is usually low in tumour tissue and high in RN, although this distinction is not universal. 73 Using MRS, Cho/Cr-ratio and Cho/N-acetyl-aspartate (NAA)-ratio were found to be higher in tumour than in RN. 74 In MET-PET, uptake is usually higher in progressive BMs than in RN; FDOPA- and FET-PET have also shown a potential discriminating ability in smaller studies.…”
Section: Treating Brain Metastasesmentioning
confidence: 99%